Expression of estrogen receptors in the hypothalamo-pituitary-ovarian axis in middle-aged rats after re-instatement of estrus cyclicity - Böttner, M. (Springer Netherlands, 2009)
During reproductive aging female rats enter an anovulatory state of persistent estrus (PE). In an animal model of re-instatement of estrus cyclicity in middle-aged PE rats we injected the animals with progesterone (0.5 mg progesterone/kg body weight) at 12:00 for 4 days whereas control animals received corn oil injections. After the last injection animals were analyzed at 13:00 and 17:00. Young regular cycling rats served as positive controls and were assessed at 13:00 and 17:00 on proestrus. Progesterone treatment of middle-aged PE rats led to occurrence of luteinizing hormone (LH), follicle stimulating hormone (FSH), and prolactin surges in a subset of animals that were denoted as responders. Responding middle-aged rats displayed a reduction of ER-β mRNA in the preoptic area which was similar to the effect in young rats. Within the mediobasal hypothalamus, only young rats showed a decline of ER-α mRNA expression. A decrease of ER-α mRNA levels in the pituitary was observed in progesterone-responsive rats and in young animals. ER-β mRNA expression was reduced in young regular cycling rats. ER-β mRNA levels in the ovary were reduced following progesterone treatment in PE rats and in young rats. Taken together our data show that cyclic administration of progesterone reinstates ovulatory cycles in intact aging females which have already lost their ability to display spontaneous cyclicity. This treatment leads to the occurrence of preovulatory LH, FSH and prolactin surges which are accompanied by differential modulation of ERs in the hypothalamus, the pituitary and the ovary.